Advanced Biomaterials for Orthopaedic Application The Challenge of New Composites and Alloys Used as Medical Devices - Affatato, Saverio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book covers a wide range of topics in the orthopaedic fields and can be used as a textbook for the ﬁnal undergraduate engineering course or as a topic on tribology at the postgraduate level. This book can serve as a useful reference for academics, tribology, and materials researchers; mechanical, materials, and physics engineers; biomedical scientists and professionals in tribology; and related industries. The scientiﬁc interest in this book will be evident for many important centres of research, including laboratories and universities throughout the world.